HISTOPATHOLOGICAL STUDY OF SALIVARY GLAND LESION - MAMTA GARG; SUNITA BIKA; SARITA PARIHAR; VEDANT GARG (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to evaluate various histopathological patterns of salivary gland lesions. Methods: The hospital-based retro-prospective observational study was conducted at the Department of Pathology, Sardar Patel Medical College and associated group of hospitals, Bikaner. This study included salivary gland biopsies/tissue following surgical resection, submitted, processed routinely, and stained with H&E stain, histopathologically diagnosed salivary gland lesions in the department of pathology. Histopathological study was carried out as records available of the previous 5 years (2017–2022). Results: We observed the number of male patients was higher than the female patients. Most of the patients in this study enrolled in 2021 followed by 2018, 2019, 2017, 2020, and 2022. The proportion of patients with poor oral hygiene was significantly higher than the proportion of patients with good oral hygiene. Pleomorphic salivary gland adenoma was the most prevalent morphological spectrum of lesions, followed by chronic sialadenitis and Warthin tumor. The frequency of benign lesions was significantly higher than malignant lesions also, the majority of parotid gland and sub-mandible gland lesions were benign. The frequency of neoplastic lesions and non-neoplastic lesions was almost similar. Conclusion: Salivary gland tumors (SGTs) are relatively more in males. The principal site for SGTs is the parotid gland in both benign and malignant tumors. PA was the most common benign SGT, and adenoid cystic carcinoma was the most frequent malignant neoplasm.